CO2‐Induced Spin‐State Switching at Room Temperature in a Monomeric Cobalt(II) Complex with the Porous Nature. Issue 26 (8th April 2020) - Nakaya, Manabu; Kosaka, Wataru; Miyasaka, Hitoshi; Komatsumaru, Yuki; Kawaguchi, Shogo; Sugimoto, Kunihisa; Zhang, Yingjie; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract: CO2 ‐responsive spin‐state conversion between high‐spin (HS) and low‐spin (LS) states at room temperature was achieved in a monomeric cobalt(II) complex. A neutral cobalt(II) complex, [Co II (COO‐terpy)2 ]⋅4 H2 O (1⋅4 H2 O ), stably formed cavities generated via π–π stacking motifs and hydrogen bond networks, resulting in the accommodation of four water molecules. Crystalline 1⋅4 H2 O transformed to solvent‐free 1 without loss of porosity by heating to 420 K. Compound 1 exhibited a selective CO2 adsorption via a gate‐open type of the structural modification. Furthermore, the HS/LS transition temperature ( T 1/2 ) was able to be tuned by the CO2 pressure over a wide temperature range. Unlike 1 exhibits the HS state at 290 K, the CO2 ‐accomodated form 1⊃CO2 ( P CO 2 =110 kPa) was stabilized in the LS state at 290 K, probably caused by a chemical pressure effect by CO2 accommodation, which provides reversible spin‐state conversion by introducing/evacuating CO2 gas into/from 1 . Abstract : All in a spin : CO2 ‐responsive spin‐state switching between high‐spin (HS) and low‐spin (LS) states at room temperature has been achieved in a monomeric cobalt(II) complex. It forms cavities generated by π–π stacking motifs and hydrogen‐bond networks.